Design of Highly Adhesive Urchin‐Like Gold Nanostructures for Effective Topical Drug Administration and Symptomatic Relief of Corneal Dryness - Sandip Ghosh; Yun‐Han Su; Chia‐Jung Yang; Jui‐Yang Lai (Small Structures)
Topical instillation of cyclosporin A (an anti‐inflammatory drug) is clinically recommended as the first‐line treatment for dry eye disease. Nevertheless, it suffers from poor ocular drug retention and cannot comprehensively address corneal dryness‐related symptoms such as oxidative stress, angiogenesis, and neurodegeneration. Inspired by nanotechnology‐mediated material/biological interactions, in this study, a highly adhesive metallic nanoplatform with an urchin‐like structure is designed for topical quercetin administration in dry eye therapy. The gold nanostructures with the most pronounced branch lengths exhibit the strongest cytoadhesion and bioadhesion capabilities, which significantly enhance the corneal retention of nano‐urchins by 150‐fold at 7 days post‐instillation compared with smooth‐surfaced gold nanoparticles. In a rabbit model of corneal dryness, topical single‐dose nanoformulation (high quercetin‐functionalized gold nano‐urchins (NU‐Q(H))) demonstrated remarkable efficacy in stimulating tear production (30‐fold improvement), inhibiting inflammatory IL‐6 expression (49‐fold improvement), attenuating pathological angiogenesis (32‐fold improvement), and promoting nerve regeneration (18‐fold improvement) compared to high quercetin‐functionalized gold nanoparticles (NP‐Q(H)). In particular, the integrity of the ocular surface, tear film, and meibomian gland is restored to levels similar to those in healthy rabbits. These findings suggest the promising potential of nanobiomaterial structural engineering in developing highly adhesive metallic nanomedicines as long‐acting eye‐drop formulations for disease treatment applications.